Experimental and Theoretical Study on Screwed Connections in Cold-Formed Steel Structure - HONGTHONG, Rattanasak; BENCHAPHONG, Apai; BENCHANUKROM, Sutera; KONKONG, Nirut (Engineering Transactions, 2019)
This research aims to study the fastening rotation behavior of cold-formed steel screw connections by experimental testing and analytical modelling. Both the experimental test and finite element results showed the failure modes of tilting and bearing failure. The rotation failure mode of the screw connection was studied by an analytical method using a spring model with screw-plate stiffness which included the bending and shear stiffness of the screw and the bearing stiffness of the screw and plates. Variation in the screw thread diameter, plate thickness, and plate thickness ratio are assigned to the spring model for the parametric study. The screw rotation or tilting was primarily controlled by the plate thickness. Presented results show that to decrease the effect of tilting failure, the end of the screw should be embedded within the thickest side of the cold-formed steel parts.